2012
DOI: 10.1371/journal.pone.0031458
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B Virus X Protein Drives Multiple Cross-Talk Cascade Loops Involving NF-κB, 5-LOX, OPN and Capn4 to Promote Cell Migration

Abstract: Hepatitis B virus X protein (HBx) plays an important role in the development of hepatocellular carcinoma (HCC). However, the mechanism remains unclear. Recently, we have reported that HBx promotes hepatoma cell migration through the upregulation of calpain small subunit 1 (Capn4). In addition, several reports have revealed that osteopontin (OPN) plays important roles in tumor cell migration. In this study, we investigated the signaling pathways involving the promotion of cell migration mediated by HBx. We repo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 47 publications
2
24
0
Order By: Relevance
“…The activation of NF-κB pathways by HBx is involved in promoting invasion and metastasis in HCC cells [21]. Therefore, we examined whether wk-MTA1 overexpression could also enhance WHx-mediated migration and invasion.…”
Section: Resultsmentioning
confidence: 99%
“…The activation of NF-κB pathways by HBx is involved in promoting invasion and metastasis in HCC cells [21]. Therefore, we examined whether wk-MTA1 overexpression could also enhance WHx-mediated migration and invasion.…”
Section: Resultsmentioning
confidence: 99%
“…HBx has been shown to activate multiple pathways to promote the degradation of the cellular matrix and decrease intercellular adhesion of liver cells. This leads to increased capacity for cell migration, demonstrating the important role of HBx in liver cancer metastasis [39]. We therefore, hypothesized that HBx could play a similar role if HBV indeed promotes PDAC.…”
Section: Discussionmentioning
confidence: 96%
“…Zhang et al reported that OPN and Capn4 proteins are involved in cell migration and affect each other in a network [16]. Therefore, we speculated that OPN might be involved in the Capn4-mediated pathobiological functions in EOC.…”
Section: Resultsmentioning
confidence: 87%
“…Rosen et al also reported that OPN can be used as a potential marker that might complement the effectiveness of CA125 as a typical marker in ovarian carcinoma [26]. Other studies have shown that OPN and Capn4 proteins are involved in cell migration, and affect each other in a network through interactions with NF-κB [16]. Accumulating evidence also indicates that OPN mediates cancer cell adhesion, migration, and proliferation through interaction with its receptor, integrin [22, 27, 28].…”
Section: Discussionmentioning
confidence: 99%